2016
DOI: 10.1016/s0140-6736(16)00258-0
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopy in recurrent in-vitro fertilisation failure (TROPHY): a multicentre, randomised controlled trial

Abstract: European Society of Human Reproduction and Embryology, European Society for Gynaecological Endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
112
1
23

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 28 publications
(36 reference statements)
2
112
1
23
Order By: Relevance
“…The same favorable results have been reported when oHS was performed within 50 days (13) or even within 6 months prior to a new ART (16). On the other hand, this impact is somehow questionable in light of the recent conflicting evidence (5,26). Further research is still needed to optimize instrumentation and timing.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The same favorable results have been reported when oHS was performed within 50 days (13) or even within 6 months prior to a new ART (16). On the other hand, this impact is somehow questionable in light of the recent conflicting evidence (5,26). Further research is still needed to optimize instrumentation and timing.…”
Section: Discussionmentioning
confidence: 88%
“…Despite several advantages, the European Society of Human Reproduction and Endocrinology does not recommend routine oHS in women undergoing ART, unless there is an apparent uterine pathology (4). Moreover, two recent randomized controlled trials have failed to show any clear benefit of this procedure either before the first IVF cycle or in repeated failed cycles (5,6). The present study aimed to evaluate the incidence of unrecognized uterine pathologies with oHS in women with RIF as well as the impact of oHS on live birth rates (LBRs) when performed prior to a new ART cycle.…”
Section: Introductionmentioning
confidence: 98%
“…Randomized, controlled studies have indicated that blastocyst transfer and salpingectomy may improve clinical outcomes in couples with RIF (2). Hysteroscopy in the preceding cycle has been reported to improve pregnancy outcomes in couples with three or more failed ET cycles (6), but this evidence has recently been contradicted by a multicenter, randomized controlled trial that showed hysteroscopy to be of no value in RIF (7). Furthermore, other techniques such as assisted hatching are still considered controversial in RIF patients (8), and the same debates continue with zygote intrafallopian transfer, cocultures, and preimplantation genetic screening (2,3,9).…”
mentioning
confidence: 99%
“…[23][24][25] The results of these studies suggest that there is no reason to perform hysteroscopy before IVF, irrespective of whether the woman is about to undergo the first cycle of IVF or if she has undergone several failed IVF attempts, as long as conventional transvaginal ultrasound shows no uterine pathology. These studies did not find an answer on the significance of hysterescopic correction of the common intrauterine lesions as polyps, submucous myomata or partial septae prior to IVF/ICSI and their relation to pregnancy rates.…”
mentioning
confidence: 99%